The performance of cryptocurrency assets under COVID19 - Maisuradze, Natia; Dudzich, Viktar; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
Despite being introduced as means of payment, cryptocurrencies quickly transformed into an investment asset class. The primary appeal of cryptocurrencies for investors lies in their innovative technology, security and anonymity provision, and high returns. The achieved popularity, increased number of users and transactions, and steep rise of its value encouraged researchers to investigate cryptocurrencies’ potential to serve as diversification assets, hedges, or safe havens. The Covid-19 pandemic provided a unique opportunity to examine cryptocurrencies’ behavior during market turbulences, as they have never experienced such shocks before. This thesis aims to investigate the resilience of these alternative assets to market shocks and analyze their possible benefits for investors during financial distress. The thesis employs three methods for empirical analysis: event study, portfolio analysis, and linear regression. These approaches provide insight into the performance of cryptocurrencies during the pandemic. Specifically, they demonstrate mixed reactions of cryptocurrencies to important milestones related to Covid-19. However, portfolio analysis confirms their diversification or hedging capabilities for investors and the potential to serve as a safe haven for S&P 500, MSCI World ETF, MSCI USA Value Factor ETF, and MSCI Germany ETFs. Notably, all kinds of media coverage affected the market capitalization of cryptocurrencies. However, if included in the portfolio, they could still enhance investors’ wealth during the pandemic.
Vedoucí práce: Viktar Dudzich
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses